2011
DOI: 10.1007/s10526-011-9425-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of predatory carabids on below- and above-ground pests and yield in strawberry

Abstract: The impact of adult carabid beetles on below-and above-ground pests and fruit yield was examined in the laboratory and a two-year strawberry field study. In the laboratory, adults of Carabus nemoralis Muller, Nebria brevicollis (F.), Pterostichus algidus LeConte, Pterostichus melanarius (Illiger), and Scaphinotus marginatus Fischer (Coleoptera: Carabidae) consumed black vine weevil, Otiorhynchus sulcatus (F.) (Coleoptera: Curculionidae) eggs, larvae and/or pupae placed on the surface. The same five carabid spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A positive correlation was found between predation rate on real prey and the abundance of ground beetles (Speight & Lawton, ; Menalled et al ., ; Prasifka et al ., ), ground‐active predators in general (O'Neal et al ., ), or predatory insects (Chang & Snyder, ) but in some cases, this was not so (Pearce & Zalucki, ; Lee & Edwards, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive correlation was found between predation rate on real prey and the abundance of ground beetles (Speight & Lawton, ; Menalled et al ., ; Prasifka et al ., ), ground‐active predators in general (O'Neal et al ., ), or predatory insects (Chang & Snyder, ) but in some cases, this was not so (Pearce & Zalucki, ; Lee & Edwards, ).…”
Section: Resultsmentioning
confidence: 99%
“…Real prey was placed mostly above‐ground (median height = 1.1 m, range = 0.15–2.68 m, n = 33) in preference to ground level ( n = 17), with a single study (Lee & Edwards, ) using below‐ground prey. In 27 articles, the height from the ground was not specified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that biological control using generalist predators, which are influenced by the plethora of abiotic and biotic factors, may have been limited [118]. In this context, Lee and Edwards [65] showed that in laboratory conditions, five different carabidae species can consume various immature stages of the black vine weevil, Otiorhynchus sulcatus (Coleoptera: Curculionidae) occurring at the soil surface, although they were not efficient in controlling the root pest in the field; this is likely due to the burring behavior of pest larvae. Moreover, in some cases, arthropod predators even produced positive effects on target pests.…”
Section: Macrofaunamentioning
confidence: 99%
“…Besides hunting their prey aboveground, adult ground beetles frequently burrow beneath the soil and could potentially suppress pests belowground (Lee and Edwards, 2012;Schwerk and Dymitryszyn, 2015).…”
Section: Introductionmentioning
confidence: 99%